2012
DOI: 10.1118/1.4725755
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of broad W/Rh and W/Al (target/filter) x-ray beams operated at 25-49 kVp through common shielding materials

Abstract: These data provide inputs for the shielding designs of x-ray imaging facilities with W-anode x-ray beams, such as from Selenia Dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
1
15
0
6
Order By: Relevance
“…Using transmission data previously published by Li et al, 8 for Hologic DBT systems, with the 40-kVp case with W/Al, this can be satisfied with ∼35 mm concrete thus should not be a concern for the shielding consideration. We need to point out a few important notes with this study.…”
Section: Discussionmentioning
confidence: 72%
“…Using transmission data previously published by Li et al, 8 for Hologic DBT systems, with the 40-kVp case with W/Al, this can be satisfied with ∼35 mm concrete thus should not be a concern for the shielding consideration. We need to point out a few important notes with this study.…”
Section: Discussionmentioning
confidence: 72%
“…These data were obtained by computational methods (Hoff Contents and Firmino, 2007;Hoff et al, 2009) or experimentally by measurements of transmitted air kerma by an ionizing chamber (Costa and Yoshimura, 2011;Ling et al, 2013). Li et al (2012) also applied a similar method for X-ray spectra typically used in mammography imaging facilities using Monte Carlo simulations. McCaffrey et al (2009) also used Monte Carlo methods for studying shielding optimization applying non-lead bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil from L. glauca leaves also showed various antibacterial effects on the common 14 kinds of bacteria reported by Liu in 2014. [5] Antitumor effect Liu [11] reported the N-methyl camphor base from L. glauca exhibited strong antitumor cell proliferation activity, especially the inhibition of colon cancer cell HT-29 and gastric cancer cell SGC-7901, which was better than the positive control drug etoposide VP-16 at the medium and high concentrations. In 2011, Wang [19] reported that the ethanol extraction of L. glauca showed inhibitory activity on the chemotaxis of human breast cancer cells.…”
Section: Antimicrobial Effectmentioning
confidence: 99%
“…Then a new alkaloid named N-cis-sinapoyltyramine (8) was reported by Yuh-Chwen Chang next year (Figure 1). [10] Liu [11] obtained magnocurarine, N-methyl litsoeine, litsoeine, boldine, norisoboldine, and noisocorydine from n-butyl alcohol and ethyl acetate parts of 95% ethanol extract of L. glauca. N-methyl litsoeine exhibited strong antitumor activity.…”
Section: Essential Oilmentioning
confidence: 99%
See 1 more Smart Citation